Rough sets and intelligent systems paradigms : International Conference, RSEISP 2007 Warsaw, Poland, June 28-30, 2007 : proceedings - RSEISP; Kryszkiewicz, Marzena (Lecture Notes in Computer Science, 2007)
This book constitutes the refereed proceedings of the International Conference on Rough Sets and Emerging Intelligent Systems Paradigms, held in Warsaw, Poland in June 2007. The conference was dedicated to the memory of Professor Zdzislaw Pawlak. Seventy-three full papers are presented, together with two keynote lectures and eleven invited papers. Each of these papers was subject to a strict editorial review.